GI Jive : An Army Bandsman in World War II - Mathias, Frank Furlong (Book collections on Project MUSE., 1982)
""Frank Mathias was a teenager in a small town when the draft swept him into the army and then halfway around the world to the jungles of the South Pacific. He served in the huge invasion force in the Battle of Manila, the deadliest single battle of the Pacific War. As an army musician attached to the 37th Infantry Division, Mathias saw the war from the bottom of the heap, where young privates lived and died. In his best selling book The GI Generation, Mathias tells of growing up in small-town America between the wars. In GI Jive he recalls the gritty experience of combat as well as the music.